Paclitaxel-Based Chemotherapy Targeting Cancer Stem Cells from Mono- to Combination Therapy - Nawara, Hend M. (Biomedicines, 2021)
Paclitaxel (PTX) is a chemotherapeutical agent commonly used to treat several kinds of cancer. PTX is known as a microtubule-targeting agent with a primary molecular mechanism that disrupts the dynamics of microtubules and induces mitotic arrest and cell death. Simultaneously, other mechanisms have been evaluated in many studies. Since the anticancer activity of PTX was discovered, it has been used to treat many cancer patients and has become one of the most extensively used anticancer drugs. Regrettably, the resistance of cancer to PTX is considered an extensive obstacle in clinical applications and is one of the major causes of death correlated with treatment failure. Therefore, the combination of PTX with other drugs could lead to efficient therapeutic strategies. Here, we summarize the mechanisms of PTX, and the current studies focusing on PTX and review promising combinations.